PERENCANAAN STRUKTUR & PONDASI GAS COMPRESSOR SHELTER STASIUN GAS BETUNG PENDOPO FIELD, PT. PERTAMINA EP ASSET 2 SUMATERA SELATAN - Triwidodo, Puput; Kristiawan, Agung; Husodo, Ibnu Toto (Universitas PGRI Semarang, 2024)
Planning for the Structure and Foundation of the Gas Compressor Shelter Betung Gas Station Pendopo Field Pertamina Asset 2 aims to upgrade facilities in order to increase production from the Pendopo Gas Station. This Gas Compressor Shelter Building is designed to be Strong and Rigid using SS400 Steel Structure. H beam structure column 400x400x13x21, WF structure rafter 400x200x9x14. In the Gas Compressor shelter building there is a Hoist Crane mechanical equipment with a capacity of 10 Tons which is based on the Beam WF-700x300x13x24. The foundation of this building uses deep foundations using square piles measuring 250x250 mm as deep as 15 meters. The quality of concrete for the foundation of the Gas Compressor Shelter uses K-350 concrete quality. From the planning above, it can be concluded that it has fulfilled the terms and conditions in Indonesian regulations and standards.